MOONLIGHTING ACTIVITIES AND LECTURERS’ WELLBEING IN NIGERIAN UNIVERSITIES - AMINI-PHILIPS, CHINYERE (Advances in Social Sciences Research Journal, 2019)
Moonlighting refers to a situation where an employee maintains a primary employment and engages in additional work for pay. It is a social phenomenon which has become prevalent in all countries and walks of life. This paper examines moonlighting activities and lecturers’ wellbeing in Nigerian universities. It began by generally reviewing literature on the meaning of moonlighting and zeroed-in on the meaning of moonlighting in the context of universities. Types and reasons for moonlighting were reviewed. The positive relationship between moonlighting and level of education as revealed in literature was highlighted, noting that the same is applicable in Nigerian universities. The study identified a number of factors that influence lecturers’ decision to moonlight which include job flexibility, employment type and lecturers’ characteristics. Moonlighting activities of lecturers identified include part time/adjunct appointment, ownership of secondary, primary and nursery schools, supermarket, etc. The paper noted that though moonlighting activities has positive consequences like monetary gain, job enrichment and fosters knowledge sharing through collaboration, negative consequences like heavy or excess workload, which impinge or affect wellbeing of lecturers as well as their universities exist. The study concluded that lecturers’ moonlighting activities are on the increase in Nigerian universities, that moonlighting activities have both positive and negative consequences for individual moonlighters and their universities. The study suggested among others that lecturers’ salaries should be reviewed upwards to discourage excessive moonlighting, universities management should formulate policies aimed at streamlining moonlighting activities, a database of all lecturers in Nigerian universities should be established to check moonlighting.